The Effect of Price, Promotion, and Ease of Use Application Online Transportation on the Usage Decision in Surabaya City - Fredianaika Istanti; Yuniawati Ekaningrum; Evada El Ummah Khoiro (Enrichment : Journal of Management, 2021)
The study aims to determine the effect of price, promotional appeal and ease of use of applications on the decision of use of online transportation. The type of research used in this study is "Explanatory Research", which is a type of research that aims to find out the small relationship and influence of one variable on other variables, as well as test the proposed hypothesis (accepted or rejected). The population in this study is the overall consumers of online motorcycle-taxi drivers (known as ojek) in Surabaya. The sampling technique used is purposive sampling, the population element is selected on the basis of its availability based on certain criteria. Test results through SPSS indicate that there is a significant positive relationship between price on usage decisions, promotion on usage decisions, and the ease of application on usage decisions. The results showed that of the four variables of price, promotion, ease of application simultaneously affect the decision to use the online transportation.